Introduction to avionics - Cundy, Dale R. (Prentice Hall, 1997)
This unique book offers a non-technical, non-manual-style presentation of basic avionics. Focusing primarily on navigation, this book provides a basic understanding of avionics. It features a section on transponder mode "s"-a newly implemented technology that is rarely treated in most other books. This book provides clear, complete coverage of flight control that simplifies often complex subject matter. Designed to serve as both a book for students and a reference for practicing technicians.